Preservation of intergranular pore in deep clastic reservoirs by rock fabric based on compaction physics simulation experiments - Guo, Huajun; Wang, Daoshen; Shan, Xiang; Peng, Bo; Zou, Zhiwen; Wu, Jin; Li, Ke (Frontiers in Earth Science, 2024)
Diagenetic physical simulation is a reliable means to study patterns of pore evolution and variations of physical properties, however, the current compaction model is mostly based on sandstone, and there is a lack of quantitative compaction and porosity reduction studies for more complex rock fabrics. In order to simulate the continuous change of intergranular porosity in the reservoir under compaction during the diagenesis of buried sedimentary strata, a self-designed diagenesis simulation experimental system was adopted. Using different modern sediment samples, the simulation experiment of mechanical compaction of glutenite was carried out. The experiment shows that during the process of mechanical compaction of glutenite, the change of porosity with depth is segmented, and there is a good logarithmic relationship between depth and porosity in the process of diagenetic compaction. The larger the grain size in the reservoir rock, the better the pore preservation capacity; When the sand particles fill the pores among gravel, stable secondary support structure formed by gravel and sand grades can effectively take over the bearing pressure, and when the sand-grade particle content is about 30%, the pressure-bearing capacity is the strongest; Intergranular heterobase filling is greater in samples with high heterobase content, high heterobasic content is not favourable to the preservation of primary pores. This study provides favorable experimental support for the preservation mechanism of deep clastic reservoir pores, and has important theoretical and practical significance for oil and gas exploration in the study area. The use of simulation experiment provides a useful idea for the evaluation and prediction of reservoirs and the search for favorable reservoir development zones in the future.